Children's labour as a risky pathways to resilience: children's growth in contexts of poor resources - Libório,Renata Maria Coimbra (2010)
In this paper we explore children's labor as a complex phenomenon encompassing risk factors on one hand and possible positive outcomes on the other. Based on the theory of resilience and on literature review that details children's own experiences of work, we show that children who are inserted in environments which are poor in social and physical resources may report labor as pathways to ensure their own resources to overcome adversity. Understanding children's subjective accounts of their experience permits us to see children's labor as a culturally-embedded construction. Though exploitation of children is not in the best interest of children, there is evidence that children use whatever opportunities are available, including labor, to search for the resources they need and negotiate for an identity as resilient. Implications for public policies and practices are discussed.